Climbing the goal ladder how upcoming actions increse level of aspiration .[article]. - Koo, Minjung
Pursuing a series of progressive (e.g.,professional) goals that form a goal ladder often leads to a trade-off between moving up to a more advanced level. This articles investigates how monitoring one's current goal in terms of remaining actions versus completed actions influences the desire to move up the goal ladder. The authors propose that a focus on remaining (vs. completed) actions increase the motivation to move up to a more advanced level, whereas the focus on completed (vs. remaining) actions increases the satisfaction derived from the present level. They find support for these predictions across several goal ladders, ranging from academic and professional ladders to simple, experimental tasks. They further find that individuals strategically attend to information about remaining (vs. completed) actions to prepare to move up the goal ladder.